2021
DOI: 10.1016/j.isci.2021.102150
|View full text |Cite
|
Sign up to set email alerts
|

Theaflavin-regulated Imd condensates control Drosophila intestinal homeostasis and aging

Abstract: Summary Black tea is the most widely consumed tea drink in the world and has consistently been reported to possess anti-aging benefits. However, whether theaflavins, one type of the characteristic phytochemicals in black tea extracts, are involved in regulating aging and lifespan in consumers remains largely unknown. In this study, we show that theaflavins play a beneficial role in preventing age-onset intestinal leakage and dysbiosis, thus delaying aging in Drosophila . Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Flavonoid compounds are divided into six subclasses, flavones, flavonols, flavanones, isoflavones, flavanols, and anthocyanins [ 228 ]. Beside the antioxidant activity, flavonoids have anti-inflammatory, vasodilator, anticoagulant, cardioprotective, anti-diabetic, neuroprotective, and anti-obesity activities, which make them of great interest as anti-aging compounds ( Table 3 ) [ 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoid compounds are divided into six subclasses, flavones, flavonols, flavanones, isoflavones, flavanols, and anthocyanins [ 228 ]. Beside the antioxidant activity, flavonoids have anti-inflammatory, vasodilator, anticoagulant, cardioprotective, anti-diabetic, neuroprotective, and anti-obesity activities, which make them of great interest as anti-aging compounds ( Table 3 ) [ 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , 257 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the mRNA levels of these AMP genes were relatively comparable between samples from c564 ts >GFP-dTrbd DNZF , c564 ts >GFP-dTrbd DLR , and the control flies (Figures 5A, B), suggesting both the NZF domain and the LR are required for dTrbd to negatively govern IMD signaling post microbial infection. Previous studies have shown that preventing the IMD signaling pathway in gut tissues positively contributes to the life longevity of Drosophila (15,(41)(42)(43). We thus sought to identify whether dTrbd modulates lifespan via multiple domains.…”
Section: Dtrbd Functions In Vivo Via Multiple Domainsmentioning
confidence: 99%
“…Studies have shown that theaflavin can delay the excessive proliferation of intestinal stem cells, prevent intestinal dysbiosis, and inhibit the activation of the Imd signaling pathway, thereby prolonging the lifespan of Drosophila. At the same time, theaflavin is effective in preventing DSS-induced colitis in mice [73]. Moreover, theaflavin can protect against oxidative stress-induced cellular senescence by activating Nrf2 in a mouse osteoarthritis model [85].…”
Section: Another Antisenescence Activity Of Flavonoidsmentioning
confidence: 96%